Inclusive Religion Education In Building Tolerance From School - Afifuddin Afifuddin; Ismail Hj. Ishak (Lembaga Sembilan Tiga Community, 2020)
This article is an in-depth study of the importance of inclusive religion education and the involvement of teachers in schools in building attitudes and tolerance lives among students. Through the search for literature and reflection on contemporary issues, the author find that inclusive education is a form of education that allows students to open their vision to an increasingly broad horizon, able to cross ethnic group boundaries or cultural and religious traditions so that they can see